(untitled) (Kerala Journal of Psychiatry, 2025)
A well-defined research framework is fundamental to conducting effective and impactful studies. This article explores the distinct yet interconnected roles of key research components: the aim, objectives, research questions, and hypothesis. The aim outlines the broad purpose of a study, while objectives delineate the measurable steps necessary to achieve the aim. Research questions specify the inquiries that guide the investigation. A hypothesis provides a testable prediction based on an assumption. Clarifying these elements is crucial for designing a coherent and focused research plan. By distinguishing and articulating each component, researchers can improve the clarity, direction, and overall quality of their studies.